Composite lubricating material, preparation method and bearing

By introducing transition metal materials and polyphenol compounds into the phenolic resin and modifying them with hyperbranched polysiloxanes to form an organic-inorganic hybrid network, the toughness and frictional performance problems of phenolic resins when synthesized under alkaline conditions are solved, and a phenolic resin composite lubricating material with high toughness and excellent frictional properties is achieved.

CN119320481BActive Publication Date: 2025-03-11JIHUA LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411872497.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

When the existing phenolic resin is synthesized under alkaline conditions, it is easy to cause the resin to shrink in large volume, hardness, poor toughness, and the water lubrication friction coefficient are too high, making it difficult to meet the requirements of large-scale water lubrication seals.

Method used

By introducing transition metal materials (such as tungsten disulfide, tungsten diselenide and molybdenum diselenide) into the phenolic resin system and mixing with polyphenol compounds, a small or single layer of nanosheets are obtained, and modified and reacted with hyperbranched polysiloxane to form an organic-inorganic hybrid network to improve the toughening and lubricating properties of the material.

Benefits of technology

The high toughness, excellent friction and mechanical properties of phenolic resin are achieved, which can meet the requirements of large-scale water lubricating sealing and avoid the problem of nanoparticle agglomeration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320481B_ABST
    Figure CN119320481B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lubricating materials, and specifically discloses a composite lubricating material, a preparation method, and a bearing. The raw materials of the composite lubricating material include a hyperbranched polysiloxane-modified wear-resistant material and a phenolic resin monomer; the hyperbranched polysiloxane-modified wear-resistant material is obtained by modifying a first material by hyperbranched polysiloxane, and the first material is obtained by mixing a transition metal material with a polyphenol compound by ball milling or mixed grinding; the transition metal material is at least one of tungsten disulfide, tungsten diselenide, and molybdenum diselenide. The composite water lubricating material prepared by the present invention has the characteristics of excellent friction performance, excellent mechanical properties, and high toughness, can meet the requirements of large-scale water lubricating seals, and solves technical problems such as particle agglomeration that are prone to occur in existing improvement methods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating materials, and in particular relates to a composite lubricating material and a preparation method thereof, and a bearing. Background Art

[0002] Phenolic resin has the advantages of high strength, good dimensional stability, excellent heat resistance and chemical corrosion resistance, but in the process of synthesizing conventional phenolic resin under alkaline conditions, a large number of phenolic hydroxyl groups are easily oxidized, resulting in a large volume shrinkage of the resin during the curing process, an increase in the degree of crosslinking, and a large hardness, poor toughness, and stress cracks are easily generated on the interface. The vibration and friction noise brought are also large. In view of the shortcomings of the existing scheme for preparing phenolic resin, there are currently several methods for modification and toughening, and reducing friction: one is to introduce internal toughening substances into phenolic resin, and the main means is to introduce flexible segments into the main chain of phenolic resin or curing agent, such as cashew nut shell oil, acrylic acid, epichlorohydrin, unsaturated fatty acids, etc. For example, the main structure of cashew nut shell oil is a phenol with a 15-carbon monoolefin or diene long chain in the meta position, so it has both the characteristics of phenolic compounds and the flexibility of aliphatic compounds, so it can be used to improve the toughness of phenolic resin and reduce friction. However, this method will also greatly reduce the glass transition temperature, elastic modulus and mechanical strength of the curing system, so that the phenolic resin curing system cannot be used as a structural material matrix. The second is to use the unique quantum size effect and surface effect of nanoparticles to improve the ability of phenolic resin curing system to induce microcracks and absorb energy; at the same time, improve the hardness of the material and reduce the friction coefficient and wear rate; commonly used nanoparticles include graphene, SiO2, CNTs, etc. However, nanoparticles have high surface energy, are easy to agglomerate in the phenolic resin matrix, and are difficult to disperse evenly. In addition, as inorganic particles, nanoparticles have poor interfacial interaction with phenolic resin, which will directly affect the performance of the curing system, such as deteriorating the processing performance, mechanical properties and friction properties of phenolic resin.

[0003] At the same time, phenolic resin material is a commonly used material for bearings, but the water-lubricated friction coefficient of phenolic resin is too high. Therefore, improving its lubrication performance is the key to meeting the requirements of large-scale water-lubricated seals. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies of the prior art and provide a composite lubricating material and a preparation method and a bearing. Based on this, the first aspect of the present invention provides a composite lubricating material, whose raw materials include a hyperbranched polysiloxane-modified wear-resistant material and a phenolic resin monomer; the hyperbranched polysiloxane-modified wear-resistant material is obtained by modifying a first material with a hyperbranched polysiloxane, and the first material is obtained by mixing a transition metal material with a polyphenol compound by ball milling or mixed grinding; the transition metal material is at least one of tungsten disulfide, tungsten diselenide and molybdenum diselenide.

[0005] The present invention first introduces a transition metal material (at least one of tungsten disulfide, tungsten diselenide and molybdenum diselenide) into a phenolic resin system, obtains a few-layer or single-layer nanosheet by mixing and grinding / ball milling with a polyphenol compound, and simultaneously realizes the modification of hydroxyl polar groups, and then introduces a hyperbranched polysiloxane on this basis to carry out a hydroxyl reaction with the hydroxyl polar groups on the surface of the nanosheet, thereby realizing the modification of the hyperbranched polysiloxane, and then uses it as one of the raw materials to carry out a curing reaction together with a phenolic resin monomer to obtain the composite lubricating material provided by the present invention.

[0006] Among them, the transition metal material introduced in the present invention is itself a good lubricating additive, so it can give the phenolic resin material excellent wear reduction and anti-wear properties; on this basis, a hyperbranched polysiloxane (a highly branched siloxane polymer containing Si-O-Si bonds with a three-dimensional dendritic structure) is introduced for further modification and participates in the curing reaction process of the phenolic resin to form an organic-inorganic hybrid network, which can effectively prevent the agglomeration of the transition metal material in the phenolic resin system. At the same time, the hyperbranched polysiloxane can serve as a transition layer between the transition metal material and the phenolic resin matrix, effectively improving the interface bonding force between the two; on the other hand, the hyperbranched polysiloxane contains a large number of active end groups, which can participate in the reaction during the curing process of the phenolic resin, thereby making the phenolic resin molecular chain more flexible (the flexibility of the Si-O-Si bond is better than the flexibility of the CC bond), thereby achieving intramolecular toughening of the phenolic resin. In order to achieve further modification of the hyperbranched polysiloxane, the present invention pre-mixes and grinds the transition metal material with the polyphenol compound / ball milling, so that the transition metal material is modified with chemically active hydroxyl groups, and also realizes the acquisition of a single-layer or few-layer nanosheet of the transition metal material, and the few-layer or single-layer transition metal material nanosheet has a unique nano-enhancement effect, which in turn can avoid the decrease in modulus and strength caused by the introduction of flexible chains into the phenolic resin molecular chain, and further enhance the toughening effect of the phenolic resin material in coordination with the intramolecular toughening effect achieved by the hyperbranched polysiloxane. Therefore, the above-mentioned various reinforcement effects cooperate with each other, and the high-toughness phenolic resin composite lubricating material with excellent friction performance and mechanical properties finally obtained by the present invention can be used as a bearing material.

[0007] In some preferred embodiments, the hyperbranched polysiloxane includes a methacryloxy group as an end group. The end group has an unsaturated carbon-carbon double bond and an ester bond (acyloxy bond). The acyloxy bond makes such silanes have a higher polarity, and the active reactivity of the silicon-acyloxy bond enables such silanes to participate in the condensation synthesis reaction of phenolic resin more efficiently and conveniently. Among them, the preparation method of the hyperbranched polysiloxane includes the following steps: mixing silane, ethanol, water and triethylamine, stirring at room temperature until the silane is fully hydrolyzed, stirring and condensing and refluxing at 70 ° C for 4 h, then cooling at room temperature, standing for 24 h, then removing triethylamine (adding activated carbon), and then performing rotary evaporation (rotary evaporation at 90 ° C for 1 h), removing ethanol and water, and obtaining HBPSi (hyperbranched polysiloxane) with a methacryloxy group as the end group. The silane may be one of 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltriisopropoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane and 3-acetoxypropyltrimethoxysilane. The number average molecular weight of the hyperbranched polysiloxane is 5000-7000.

[0008] In some preferred embodiments, the polyphenol compound is one of tannic acid, catechin, anthocyanin and quercetin. More preferably, the polyphenol compound is tannic acid.

[0009] In some preferred embodiments, the mass ratio of the polyphenol compound to the transition metal material is (1-5): 1. More preferably, the mass ratio is 2:1.

[0010] In some preferred embodiments, the mass of the hyperbranched polysiloxane modified wear-resistant material is 1 wt%-15 wt% of the mass of the phenolic resin monomer. More preferably, the mass of the hyperbranched polysiloxane modified wear-resistant material is 10 wt% of the mass of the phenolic resin monomer.

[0011] The composite lubricating material is prepared from hyperbranched polysiloxane modified wear-resistant material and phenolic resin monomers (phenol and formaldehyde) under the action of a catalyst; the catalyst is NaOH, Ba(OH) 2 and NH 3 ·H 2 O; the molar ratio of phenol to formaldehyde is greater than 1, specifically 1.2-1.4.

[0012] A second aspect of the present invention provides a method for preparing the composite lubricating material, comprising the following steps:

[0013] S1, mixing the transition metal material and the polyphenol compound, and ball milling or grinding to obtain the first material;

[0014] S2, reacting the first material with the hyperbranched polysiloxane in an alcohol-water system to obtain the hyperbranched polysiloxane-modified wear-resistant material;

[0015] S3, mixing the hyperbranched polysiloxane modified wear-resistant material with phenolic resin monomer to obtain the composite lubricating material.

[0016] Among them, the specific process of S1 includes: mixing the above-mentioned transition metal material with the above-mentioned polyphenol compound, using zirconium dioxide ball milling beads at 500 rpm for 12 hours to obtain the above-mentioned first material; wherein, forward rotation for 3 minutes, stop for 3 minutes, reverse rotation for 3 minutes, and stop for 3 minutes, which is one cycle.

[0017] The single-layer or few-layer transition metal material nanosheet modified with polyphenol compounds obtained in S1 (ie, the first material) is washed three times with water, then centrifuged and precipitated, and dried.

[0018] Among them, the specific process of S2 includes: dispersing the above-mentioned first material into an alcohol-water system (which can be ethanol and water, and the volume ratio of ethanol and water is 9:1), ultrasonicating for 10 min, the mass concentration of the above-mentioned first material is 10 mg / mL, and then adding the above-mentioned hyperbranched polysiloxane, the mass ratio of the above-mentioned hyperbranched polysiloxane to the above-mentioned first material can be 1:1, and then condensing and refluxing at 90°C for 4 h; centrifugal precipitation and drying to obtain the above-mentioned hyperbranched polysiloxane-modified wear-resistant material.

[0019] Among them, the specific process of S3 includes: ultrasonically dispersing the above-mentioned hyperbranched polysiloxane modified wear-resistant material in phenol, adjusting the pH to 9-10, adding a formaldehyde solution with a mass concentration of 36%-40%, and then reacting at 70°C for 60 minutes, and then adjusting to 95°C-100°C for constant temperature reaction for 30 minutes to obtain a phenolic resin prepolymer solution; then pouring the above-mentioned phenolic resin prepolymer solution into a mold, hot pressing and curing it, and obtaining the above-mentioned composite lubricating material.

[0020] The pressure of the hot pressing curing is 10 MPa; the hot pressing curing is completed under the conditions of a temperature rising program, and the temperature rising program includes: keeping warm at 70°C for 15 min, keeping warm at 100°C for 15 min, keeping warm at 120°C for 15 min, and keeping warm at 140°C for 15 min.

[0021] A third aspect of the present invention provides a bearing comprising the composite lubricating material.

[0022] The beneficial effects of the present invention are as follows: the composite water-lubricating material prepared by the present invention has the characteristics of excellent friction performance, excellent mechanical properties and high toughness, can meet the requirements of large-scale water-lubricating seals, and solves technical problems such as particle agglomeration that are prone to occur in existing improvement methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Shown are the transmission electron microscope images and corresponding EDS element scanning images of the tannic acid modified tungsten disulfide nanosheets synthesized in Example 1;

[0024] Figure 2 Shown is the GPC result diagram of the hyperbranched polysiloxane synthesized in Example 1;

[0025] Figure 3 Shown is a TGA curve of the hyperbranched polysiloxane modified wear-resistant material synthesized in Example 1;

[0026] Figure 4 Shown is the GPC result diagram of the hyperbranched polysiloxane synthesized in Example 2;

[0027] Figure 5 Shown is the GPC result diagram of the hyperbranched polysiloxane synthesized in Example 3;

[0028] Figure 6 Shown are the transmission electron microscope images of the catechin-modified tungsten disulfide nanosheets synthesized in Example 5 and the corresponding EDS element scanning images. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments and drawings to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0030] Example 1

[0031] A composite lubricating material, the preparation method of which comprises the following steps:

[0032] (1) Take 100 mL of 3-methacryloxypropyltriethoxysilane, 300 mL of ethanol, 40 mL of water and 3 mL of triethylamine and mix them in a three-necked flask equipped with a thermometer and a condenser; stir at room temperature for 15 min. After the silane is fully hydrolyzed, transfer the three-necked flask to a water bath and stir, condense and reflux at 70 °C for 4 h; then move to room temperature to cool and let stand for 24 hours. Add activated carbon to remove triethylamine; then perform rotary evaporation (rotary evaporation at 90 °C for 1 h) to remove ethanol and water from the mixed liquid to obtain the desired HBPSi (hyperbranched polysiloxane) with methacryloxy as the end group. The GPC data results are as follows: Figure 2 As shown (wherein the ordinate represents the voltage value converted from the difference in refractive index of the liquid on the sample side and the reference side flowing through the detection cell); from the GPC data, it can be seen that the measured number average molecular weight (Mn) of the hyperbranched polysiloxane is 5956, and the polymer dispersibility index (PDI) is 1.80.

[0033] (2) 15 g of tungsten disulfide and 15 g of tannic acid were placed in a 250 mL zirconium dioxide ball mill, and zirconium dioxide ball mills were used. At a speed of 500 rpm, the mill was rotated forward for 3 minutes, stopped for 3 minutes, reversed for 3 minutes, and stopped for 3 minutes. This was a cycle and the milling lasted for 12 hours. Tannic acid-modified tungsten disulfide nanosheets (i.e., the first material) were obtained. The nanosheets were then washed three times with deionized water, centrifuged and dried. The transmission electron microscope image and the corresponding EDS element scanning image are shown in the figure. Figure 1 As shown; From the figure, we can see that the four elements W, S, O, and C are evenly distributed on the surface of the material. The W and S elements come from WS 2 In itself, O and C come from the grafted tannic acid molecules; because the copper grid used for TEM photography is covered with a carbon film, carbon elements exist throughout the entire image; but the carbon elements in the sample of the first material are more concentrated, and it can be confirmed that the sample contains carbon elements.

[0034] (3) Disperse the dried first material into a mixed solution of ethanol and water, the volume ratio of ethanol and water is 9:1, and ultrasonicate for 10 min, wherein the mass concentration of the first material is 10 mg / mL; then add HBPSi synthesized in step (1), the mass ratio of the first material to HBPSi is 1:1, and condense and reflux for 4 h under heating conditions of 90 °C, then centrifuge and precipitate, and dry in a vacuum oven to obtain the first material modified by hyperbranched polysiloxane (i.e. HBPSi), i.e. hyperbranched polysiloxane modified wear-resistant material. Its TGA curve is as follows: Figure 3 As shown by Figure 3 It can be seen that pure WS 2There is basically no weight loss during the heating process of 30 ℃-800 ℃, indicating that its properties are stable; while the hyperbranched polysiloxane modified wear-resistant material has three obvious weight loss steps. Within 100 ℃, it may be due to some free small molecules or adsorbed water; between 100 ℃-300 ℃, it is mainly from the decomposition of tannic acid molecular chains; between 300 ℃-600 ℃, it is mainly from the decomposition of hyperbranched polysiloxane molecular chains; this also proves that in the hyperbranched polysiloxane modified wear-resistant material, WS 2 The surface is modified with tannic acid molecules and hyperbranched polysiloxane molecules.

[0035] (4) Ultrasonic dispersion of the hyperbranched polysiloxane modified wear-resistant material obtained in step (3) into phenol for 15 min, then adjusting the pH value of the system to 10 with a 20% sodium hydroxide aqueous solution, adding a 36% formaldehyde solution dropwise, reacting at 70°C for 60 min, and then isothermal reaction at 100°C for 30 min to obtain a phenolic resin prepolymer solution; wherein the molar ratio of phenol to formaldehyde is 1:1.3, and the mass of the hyperbranched polysiloxane modified wear-resistant material is 10 wt% of the mass of the phenolic resin monomer (i.e., phenol and formaldehyde); then pouring the phenolic resin prepolymer solution into a mold and hot pressing and curing to obtain the composite lubricating material; wherein the pressure of the hot pressing and curing is 10 MPa; and completing the hot pressing and curing under the conditions of a heating program, wherein the heating program includes: keeping warm at 70°C for 15 min, keeping warm at 100°C for 15 min, and keeping warm at 120°C for 15 min. min, and keep at 140 ℃ for 15 min.

[0036] Example 2

[0037] A composite lubricating material, which differs from Example 1 in that: in step (1), the mixture is stirred and condensed under reflux at 70°C for 8 h; the rest is the same as Example 1. The GPC data results are as follows: Figure 4 As shown; from the GPC data, it can be seen that the measured number average molecular weight of the hyperbranched polysiloxane is 7437 and the polymer dispersibility index is 2.47.

[0038] Example 3

[0039] A composite lubricating material, which differs from Example 1 in that 3-acetoxypropyltrimethoxysilane is used to replace 3-methacryloxypropyltriethoxysilane in Example 1 for synthesizing hyperbranched polysiloxane; the rest is the same as Example 1. The GPC data results are as follows Figure 5 As shown; from the GPC data, it can be seen that the measured number average molecular weight of the hyperbranched polysiloxane is 6040 and the polymer dispersibility index is 1.74.

[0040] Example 4

[0041] A composite lubricating material, which differs from Example 1 in that tungsten diselenide is used to replace the tungsten disulfide in Example 1; the rest is the same as Example 1.

[0042] Example 5

[0043] A composite lubricating material, which differs from Example 1 in that catechin is used to replace the tannic acid in Example 1; the rest is the same as Example 1. The transmission electron microscope image of catechin-modified tungsten disulfide nanosheets and the corresponding EDS element scanning image are shown in Figure 6 As shown; From the figure, we can see that the four elements W, S, O, and C are evenly distributed on the surface of the material. The W and S elements come from WS 2 The O and C come from the grafted catechin molecules. Because the copper grid used for TEM photography is covered with a carbon film, carbon is present throughout the image. However, the carbon content of the catechin-modified tungsten disulfide nanosheet sample is more concentrated and the color of the element is brighter, which confirms that the sample contains carbon.

[0044] Example 6

[0045] A composite lubricating material, which differs from Example 1 in that the mass of the hyperbranched polysiloxane modified wear-resistant material is 5 wt % of the mass of the phenolic resin monomer (i.e., phenol and formaldehyde); the rest is the same as Example 1.

[0046] Example 7

[0047] A composite lubricating material, which differs from Example 1 in that the mass of the hyperbranched polysiloxane modified wear-resistant material is 15 wt % of the mass of the phenolic resin monomer (ie, phenol and formaldehyde); the rest is the same as Example 1.

[0048] Comparative Example 1

[0049] A composite lubricating material, which differs from Example 1 in that steps (2) to (3) are not performed, and step (4) is performed directly after HBPSi synthesized in step (1) is used to replace the hyperbranched polysiloxane-modified wear-resistant material in step (4).

[0050] Comparative Example 2

[0051] A composite lubricating material, which differs from Example 1 in that steps (1) to (3) are not performed, and step (4) is performed directly after replacing the hyperbranched polysiloxane-modified wear-resistant material in step (4) with tungsten disulfide.

[0052] The composite lubricating materials prepared in Examples 1-7 and Comparative Examples 1-2 were used as bearing samples to test mechanical properties and friction properties, respectively. The results are shown in Tables 1 and 2.

[0053] Table 1 Mechanical properties data

[0054] sample Tensile strength (MPa) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 9.05±0.45 6.92±0.45 Example 2 7.89±0.34 6.58±0.39 Example 3 8.33±0.37 6.03±0.33 Example 4 7.91±0.29 6.18±0.47 Example 5 8.40±0.25 5.77±0.28 Example 6 7.54±0.39 5.98±0.40 Example 7 6.98±0.43 6.16±0.39 Comparative Example 1 6.28±0.22 4.12±0.45 Comparative Example 2 5.57±0.47 3.54±0.52

[0055] It can be seen from the comparison between Example 1 and Example 2 that the molecular weight of the synthesized hyperbranched polysiloxane in Example 1 is moderate, the dispersibility index is smaller, and the molecular weight of the synthesized hyperbranched polysiloxane is more uniform, so the hyperbranched polysiloxane is more evenly dispersed in the phenolic resin matrix, and the toughening effect on the phenolic resin is more significant. It can be seen from the comparison between Example 1 and Example 3 that the hyperbranched polysiloxane synthesized by 3-methacryloxypropyltriethoxysilane has a better toughening effect. It can be seen from the comparison between Example 1 and Example 4 that the toughening effect of tungsten disulfide is better because its density is lower and the nanosheets contained in the same mass are more, resulting in a more significant nano-enhancement effect. It can be seen from the comparison between Example 1 and Example 5 that the effect of tannic acid modification is better than catechins, because tannic acid contains more hydroxyl groups, making it easier to graft to the surface of transition metal nanosheets. It can be seen from the comparison between Example 1 and Example 6 and Example 7 that increasing the addition amount of modified transition metal nanosheets is helpful to improve the mechanical properties of phenolic resin; but if the content is too high, even after surface modification, agglomeration will still occur, resulting in a reduction in tensile strength. It can be seen from the comparison between the embodiment and the comparative example that the interfacial interaction force with the phenolic resin matrix is ​​generally improved by the transition metal nanosheets modified by hyperbranched polysiloxane, and both tensile strength and impact strength are improved simultaneously. In comparative example 2, if only hyperbranched polysiloxane is added, the toughening effect on phenolic resin is limited. Experimental data show that embodiment 1 has the maximum tensile strength and impact strength, proving that hyperbranched polysiloxane and transition metal nanosheets have a good synergistic toughening effect, and 10 wt% is the optimal addition amount.

[0056] Table 2 Friction and wear data

[0057]

[0058] Experimental data show that Example 1 has the minimum friction coefficient and wear rate, proving that hyperbranched polysiloxane and transition metal nanosheets have good synergistic effects of reducing friction coefficient and reducing wear rate. It can be seen from the comparison of the embodiment and the comparative example that the use of hyperbranched polysiloxane and transition metal nanosheets alone has limited impact on the friction performance of phenolic resin. However, by adding transition metal nanosheets modified by polyphenol compounds, the friction coefficient and wear rate can be significantly reduced, especially tungsten disulfide modified by tannic acid. It can be seen from the comparison of embodiment 1 and embodiment 4 that the toughening effect of tungsten disulfide is better, because sulfur element is easier to transfer to the grinding head than selenium element, forming a transfer film, thereby reducing friction coefficient and wear rate. Appropriate addition of transition metal nanosheets modified by polyphenol compounds helps to form a transfer film, thereby reducing friction and wear. When the transition metal nanosheets modified by polyphenol compounds are added in excess, it is easy to cause agglomeration, forming more serious abrasive wear, resulting in an increase in friction coefficient and wear rate.

[0059] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. A composite lubricating material, characterized in that: The raw materials include hyperbranched polysiloxane modified wear-resistant material and phenolic resin monomer; the hyperbranched polysiloxane modified wear-resistant material is obtained by modifying a first material with hyperbranched polysiloxane, and the first material is obtained by mixing a transition metal material with a polyphenol compound by ball milling or mixed grinding; the transition metal material is at least one of tungsten disulfide, tungsten diselenide and molybdenum diselenide; The hyperbranched polysiloxane includes methacryloxy groups as terminal groups; the preparation method of the hyperbranched polysiloxane includes the following steps: mixing silane, ethanol, water and triethylamine, stirring at room temperature until the silane is fully hydrolyzed, stirring and condensing and refluxing at 70°C for 4 hours, then cooling at room temperature, standing for 24 hours, then removing triethylamine, and then performing rotary evaporation to remove ethanol and water to obtain the hyperbranched polysiloxane with methacryloxy groups as terminal groups; The mass ratio of the polyphenol compound to the transition metal material is (1-5): 1; The mass of the hyperbranched polysiloxane modified wear-resistant material is 1 wt%-15wt% of the mass of the phenolic resin monomer; The phenolic resin monomers are phenol and formaldehyde.

2. The composite lubricating material according to claim 1, characterized in that: The polyphenol compound is one of tannic acid, catechin, anthocyanin and quercetin.

3. The composite lubricating material according to claim 2, characterized in that: The polyphenol compound is tannic acid.

4. The composite lubricating material according to claim 1, characterized in that: The mass ratio of the polyphenol compound to the transition metal material is 2:

1.

5. The composite lubricating material according to claim 1, characterized in that: The mass of the hyperbranched polysiloxane modified wear-resistant material is 10 wt % of the mass of the phenolic resin monomer.

6. A method for preparing the composite lubricating material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing the transition metal material and the polyphenol compound, and ball milling or grinding to obtain the first material; S2, reacting the first material with the hyperbranched polysiloxane in an alcohol-water system to obtain the hyperbranched polysiloxane-modified wear-resistant material; S3, mixing and reacting the hyperbranched polysiloxane modified wear-resistant material with a phenolic resin monomer to obtain the composite lubricating material.

7. A bearing, characterized in that: The composite lubricating material comprises the composite lubricating material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Hyperbranched polysiloxane modified oxidized nanocellulose aerogel as well as preparation method and application thereof

    CN116769229A

  • Preparation method of hyperbranched polysilane modified phenolic resin

    CN116948120A